2014
DOI: 10.1155/2014/927576
|View full text |Cite
|
Sign up to set email alerts
|

Influence on Therapeutic Decision Making of SPECT-CT for Different Regions of the Foot and Ankle

Abstract: Background. Single-photon emission computed tomography and computed tomography (SPECT-CT) has a high impact on diagnosis and treatment decision of different joints. The aim of this study was to evaluate whether there is a different gain of SPECT-CT for different foot regions. Material and Methods. We retrospectively identified 86 patients who received a SPECT-CT of the foot and ankle between April 2011 and December 2012. We divided all patients into the following subgroups: ankle (group 1), subtalar (group 2),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…The improvement in patients was clinically demonstrated by the efficacy of hESC therapy in treating LD patients, this was assessed by evaluating the change in SPECT scan at the end of treatment. [16][17][18]…”
Section: Materials and Methods Casesmentioning
confidence: 99%
“…The improvement in patients was clinically demonstrated by the efficacy of hESC therapy in treating LD patients, this was assessed by evaluating the change in SPECT scan at the end of treatment. [16][17][18]…”
Section: Materials and Methods Casesmentioning
confidence: 99%
“…This coregistration imaging modality has evolving and expanding indications in the foot and ankle . It has been useful in evaluating degenerative joints in the ankle and midfoot, painful total ankle replacements, malalignment, osteochondral lesions, diabetic foot infection, accessory bones, stress fractures, tarsal coalitions, and impingement and soft tissue pathology …”
Section: Discussionmentioning
confidence: 99%
“…[67891011121617] Mohan et al . reported that SPECT/CT influenced management in 10/19 (53%) patients in whom follow-up data were available.…”
Section: Added Value Of Single-photon Emission Computed Tomography/comentioning
confidence: 99%